การวิเคราะห์ปัจจัยที่ส่งผลต่อบทบาทที่ปฏิบัติจริง ของผู้บริหารโรงเรียนมัธยมศึกษา สังกัดกรมสามัญศึกษา ที่ผ่านเกณฑ์มาตรฐาน - ธีรพนธ์ คงนาวัง (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objective of this study was to analyze the factors affecting the actual roles of the secondary school administrators under the jurisdiction of the General Education Department. The hypothesis was that the factors affecting the actual roles were divided into 4 groups as follows: 1) the factors of individual characteristics; the factors of working group; the factors of organizational and the external environment factors . 396 secondary school administrators were the sample group who answered the questionnaire. Frequencies, percentage, arithmetic mean, standard deviations, correlation coefficient and multiple regression coefficient were the tools used to analyze the data from the questionnaire. The findings were as follows: 1) There were four groups of factors affecting the six actual roles of the secondary school administrators : the factors of individual; the factors of working group; the organizational factors and the external environmental factors. 2) There were six sub-factors which affecting the actual roles of the secondary school administrators as follows: 3 factors which were statistically significant at .01 were general management skills of administrators, the cooperation given by personnel to the administrators, and departmentalization; 3 factors which were statistically significant at .05 were language abilities of administrators, academic emphasis and values of parents.